HUBUNGAN TINGKAT PENGETAHUAN BASIC LIFE SUPPORT (BLS) DENGAN MOTIVASI PEMBERIAN PERTOLONGAN PADA KORBAN BENCANA OLEH TIM SEARCH AND RESCUE (SAR) DAERAH ISTIMEWA YOGYAKARTA(DIY) - Rizal Ismail (PSIK 15 UMY 626, 2015)
Natural disasters are events that can cause fatalities. Natural disasters that occurred in Daerah Istimewa Yogyakarta (DIY) from 2002 to 2011 was 89 disastrous events that had taken the dead and missing as many as 5023 lives and affected 1,582,137 souls. To reduce casualties in the event of natural disaster preparedness team needed as a team Search And Rescue (SAR), which served to evacuate and provide basic life support to victims. Additionally, high motivation to help the victims also greatly affect the least number of deaths due to natural disasters. Objective: To determine the level of knowledge BLS relationship with the motivation of the relief to the victims of natural disasters by DIY Rescue team. Methods: This study was observational whit cross sectional analytic approach conducted in november until december 2015. The sampling technique purposive sampling method, acquired as many as 38 people. Collecting data using questionnaires and conducted univariate and bivariate analysis using chi-square test. Results: The research result of basic life support knowladge level, good =(57,89%), bad = (42,11%). The motivation level to help victim of disaster, high = (52,63%), low = (47,37%). Scor Ï-value = 0.171. Conclusion: There was no significant relationship between the level of knowledge of basic life support and motivation of the relief to the victims of the disaster by DIY Rescue team.